A review on the use of radionuclide imaging techniques to detect margin positivity in intraoperative specimens during breast-conserving surgery - Sinha, Aaditya; Purushotham, Arnie (Frontiers in Medical Engineering, 2025)
IntroductionAchieving negative margins during breast-conserving surgery (BCS) for breast cancer is critical to reduce re-excision rates and minimise local recurrence. Intraoperative imaging techniques using radiotracers such as 18F-fluorodeoxyglucose (18F-FDG) offer a promising solution. When administered intravenously, 18F-FDG accumulates preferentially in malignant tissues due to their elevated glycolytic activity, enabling molecular imaging of tumour margins. Technologies such as Cerenkov Luminescence Imaging (CLI), Flexible Auto-Radiography (FAR), and intraoperative PET/CT systems have emerged as tools to visualise radiotracer distribution in excised breast tissue, offering real-time insight into margin status.Materials and methodologyCLI operates on the principle of detecting visible light photons generated by positrons from 18F-FDG travelling faster than light in tissue. FAR captures beta particles via a scintillating film to yield high-resolution surface maps of tracer activity. These modalities were evaluated both independently and in combination (CLI-FAR) using the LightPath® system, while the XEOS AURA 10 system was utilised for intraoperative PET/CT imaging. A series of feasibility studies and interventional trials assessed their diagnostic performance in real-time margin assessment during BCS.ResultsGrootendorst et al. (J. Nucl. Med., 2017, 58(6), 891–898) demonstrated that CLI achieved 89% sensitivity and 95% specificity in identifying positive margins in a cohort of 12 patients. Jurrius et al. (EJNMMI Res., 2021, 11(1)) reported 81.7% sensitivity and 46.2% specificity with FAR in 66 patients. The CLI-FAR technique, by Sinha et al. (Radiol. Adv., 2024, 1(2)), yielded 76.9% sensitivity and 97.8% specificity, reducing re-excision rates by 69%. PET/CT-based intraoperative imaging using the AURA 10 device, as evaluated by Crem et al. (ESMO Open, 2024, 9), achieved 91% sensitivity and 94% specificity, while Göker et al. (Acta Chir. Belg., 2020, 120(5), 366–374) reported 79% sensitivity and 72% specificity using micro-PET/CT. Radiation exposure to surgical staff across studies remained low (15–38 µSv), and imaging added minimal time to operative workflows.ConclusionRadionuclide-based intraoperative specimen imaging offers a viable, real-time solution for margin assessment in BCS. Techniques such as CLI, FAR, and intraoperative PET/CT demonstrate a strong correlation with histopathology, with the potential to significantly reduce re-excision rates. Challenges remain in imaging larger specimens and tumours with low metabolic activity. However, integrating these technologies into surgical practice presents a transformative opportunity for precision-guided oncologic surgery.